Development of Fuzzy Database Systems - Phang, K. K. (Malaysian Journal of Computer Science, 1997)
Describes i) necessity of fuzzy DataBase ii) techniques used in the storage and retrieval of fuzzy data in a DataBase or information retrieval system iii) DataBase framework for fuzzy DataBase and iv) the advantages of using object-oriented DataBase framework in fuzzy DataBase. A prototype of fuzzy object-oriented DataBase system, (FOODS), has been developed to demonstrate the feasibility of fuzzy object-oriented DataBase system.